Flip Science Module Using an Integrated PBL Model for Market Snacks to Improve Problem Solving Skills - Ragil Saputri; Insih Wilujeng; Suyanta; Raudhah Maharana Fahmi (Postgraduate, University of Mataram, 2024)
Science education at junior high school level has a strategic role in forming students' problem-solving abilities. This research aims to see the effect of the Flip science module using a PBL model integrated with market snacks to improve middle school students' problem solving abilities. The experimental method carried out in this research used a one group pretest-posttest design. This research was conducted at SMPN 6 Yogyakarta in the even semester of 2023. This research was conducted in one class, namely class VIII D. The sampling technique used cluster random sampling. random sampling. The class is determined by the school with the assumption that the class is assumed to have the same abilities based on even gender. The data analysis technique for measuring problem solving abilities uses a normalized gain score. The research results show that the Science flip module flip module using a PBL model integrated with market snacks can improve students' problem solving abilities based on the results of a gain score of 0.7 in the high category. The results of this research can be used by teachers to improve the problem solving abilities of junior high school students in science subjects